HYDROCYCLONE TERBUKA UNTUK PENGENDAPAN PARTIKEL FLOKULEN - Syamsul Huda; Ali Masduqi (Universitas Kebangsaan, 2019)
Open hydrocyclone is a separation unit between solid and liquid based on differences in density and centrifugal speed. In this study, an open hydrocyclone unit is used to settle type II particles or flocculent particles from the coagulation-flocculation process. The study of open hydrocyclone aims to determine the optimal performance of the unit. This research examines the effect of variations in surface loading and turbidity levels on the efficiency of turbidity reduction. Surface loading variation values used are 2.5, 3, and 3.5 m3/m2.hour. While variations in turbidity levels used are 30-45, 55-90, and 100-180 NTU. The unit used in this study is a PVC pipe unit as a flash mixing unit, a circular hose as a slow mixing unit, and an open hydrocyclone as a settling unit. The operating unit is carried out continuously for 20 minutes after operation in a steady state. During operation, the discharge in the hydrocyclone underflow is always monitored so that no disturbance occurs when the settling flocculent particles reach a maximum. The results showed that surface loading of 2.5 m3/m2.hour (1.31 liters/minute discharge) produced the highest turbidity removal efficiency with an efficiency value of 89%. The removal at the initial turbidity level of 100-180 NTU has the highest efficiency of 89%. Keyword: Hydrocyclone, Turbidity, Surface Loading, Flocculent Particle